Issues on fulfillment of zakat through online payment / Nur Amalina Mohd Roni - Mohd Roni, Nur Amalina (2013)
Zakat is the third pillars of Islam which means purification, goodness and blessing. It is an act of worship and like any other act of worship it is solely for Allah. The purpose of the study is to analyze few issues on zakat transaction through online payment such as validity of payment through virtual ijab (offer) and qabul (acceptance) and fulfillment of zakat from conventional banking account. Data collection will be conducted through interview with selected respondent from Pusat Zakat Negeri Johor as well as secondary sources such as books, journals and conference proceedings. This study concludes that zakat transaction through online payment in Malaysia fulfilled the conditions stipulated by Muslim scholar but has to intensify its effort to rise up the level of awareness among Muslim to conclude the transaction via online.